Urbanization and Work Ethic Culture Case Study: Sindang Workers - Adi Perdana, Kevin; Sinaga, Rinaldo Sutanto (UI Scholars Hub, 2024)
Background: Urbanization changes the demographic structure and lifestyle, and drives economic growth and the construction sector including Sindang Workers. Sindang Workers from Sindanglaut, Cirebon, play an important role in urban projects with a high work ethic. This study then links their work culture with the theory of social capital. Aims: The study examines how social capital influences the work ethic culture of Sindang Workers through indicators of migration, work ethic culture, and work discipline. Methods: This study uses a qualitative approach such as interviews and field observations to understand the factors driving the work ethic of Sindang Workers. Results: The results of the study show that Sindang Workers who are motivated by a solid work system demonstrate high discipline, effective communication, and a strong work ethic. They work independently but collaboratively, ensuring productivity and work quality remain high. However, there are variations in individual motivation. This answers the theory of social capital that work ethic is a response of Sindang Workers in a cultural context to adapt to the Sindang Worker community in urban areas. Conclusion: To improve the efficiency and welfare of Sindang Workers, it is necessary to improve work facilities, communication, and collaboration. In addition, to create an inclusive work environment without discrimination, it is necessary to ensure that all workers feel valued and have equal opportunities.